1984
DOI: 10.1159/000260777
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Content of Enamel during Treatment and 2 Years after Discontinuation of Treatment with Fluoride Varnishes

Abstract: The aim of this study was to determine the fluoride content of enamel during and after treatment with two fluoride varnishes in children with lifelong exposure to fluoridated drinking water. The varnishes were applied semiannually using the half-mouth technique. The fluoride content of enamel in upper bicuspids was determined using the acid etch biopsy twice during the 3-year treatment period and 2 years after the last treatment. The results of all determinations showed significantly higher values for fluoride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…Despite this limitation, Duraphat varnish achieved a caries reduction of 30%, but the caries reduction by Fluor Protector varnish was not significant, probably because fluoride from Fluor Protector had moved to the control side of the mouth. Fluor Protector varnish deposited significantly more fluoride in the enamel than Duraphat varnish, a finding which has also been reported in other studies [17][18][19]. The reason for this finding is unclear.…”
Section: Early Studies Of the Efficacy Of Fluoride Varnishessupporting
confidence: 67%
“…Despite this limitation, Duraphat varnish achieved a caries reduction of 30%, but the caries reduction by Fluor Protector varnish was not significant, probably because fluoride from Fluor Protector had moved to the control side of the mouth. Fluor Protector varnish deposited significantly more fluoride in the enamel than Duraphat varnish, a finding which has also been reported in other studies [17][18][19]. The reason for this finding is unclear.…”
Section: Early Studies Of the Efficacy Of Fluoride Varnishessupporting
confidence: 67%
“…Considering fluoride varnishes, Fluor Protector has clearly deposited more fluoride in the enamel than Duraphat, but it has not been clinically more effective (Seppa, 1991). 5) (Seppa, 1984;Seppa et al, 1984). 4), caries prevention did not persist during this time with either of the varnishes (Fig.…”
Section: Gaardetalmentioning
confidence: 85%
“…Since no calcium fluoride could be detected, Bang and Kim (1973), who found a significantly elevated fluoride concentration in the surface enamel one week after application of Duraphat in vivo, suggested that the fluoride was retained as fluorapatite. The firmly bound fluoride which is observed in connection with Duraphat (and 2% NaF) treatment (Bang and Kim, 1973;Petersson, 1975;Seppa, 1984;0gaard et al, 1984) is most likely formed later as a result of remineralization during pH cycling in plaque (R0lla, 1988). Furthermore, Cruz and co-workers (1992b) showed that no firmly bound fluoride was present immediately after treatment.…”
Section: Calcium Fluoride Formation During Professional Topical Fluormentioning
confidence: 99%
“…13 Fluoride varnish needs to be reapplied to maintain its caries-preventive effect. 14,15 The only disadvantage of fluoride varnishes is they cause a temporary change in tooth color and perceptible color changes in some restorative materials. 16 Few studies have investigated the effect of fluoride varnishes on restorative materials.…”
Section: Introductionmentioning
confidence: 99%